An Ethanolic Extract of Cucurbita pepo L. Seeds Modifies Neuroendocrine Disruption in Chronic Stressed Rats and Adrenal Expression of Inflammatory Markers and HSP70 - Almohaimeed, Hailah M.; Hamed, Shereen; Seleem, Hanan S.; Batawi, Ashwaq H.; Mohammedsaleh, Zuhair M.; Balgoon, Maha Jameal; Ali, Soad S.; Al Jaouni, Soad; Ayuob, Nasra (Frontiers in Pharmacology, 2021)
Background: Pumpkins (Cucurbita pepo L.) were described to have antioxidant, anti-inflammatory, anti-fatigue, and antidepressant-like effect. The adrenal gland is an important stress-responsive organ that maintains homeostasis during stress. Objectives: This study aimed to assess the efficacy of the administration of Cucurbita pepo L. (CP) extract in relieving behavioral, biochemical, and structural changes in the adrenal gland induced by exposure to chronic unpredictable mild stress (CUMS) and to explore the mechanism behind this impact. Materials and Methods: Forty male albino rats were divided into 4 groups (n = 10): control, CUMS, fluoxetine-treated, and CP-treated groups. Behavioral changes, corticosterone level, pro-inflammatory cytokines TNF-α and IL-6, and oxidant/antioxidant profile were assessed in the serum at the end of the experiment. Adrenal glands were processed for histopathological and immunohistochemical assessment. Gene expression of caspase-3 and Ki67 and heat shock protein 70 (HSP70) were assessed in adrenal glands using RT-PCR. Results: The CP extract significantly reduced the corticosterone level (p < 0.001), immobility time (p < 0.001), and inflammatory and oxidative changes associated with CUMS-induced depression compared to the untreated group. The CP extract alleviated CUMS-induced adrenal histopathological changes and significantly reduced apoptosis (p < 0.001) and significantly upregulated antioxidant levels in the serum. Conclusion:Cucurbita pepo L. effectively ameliorated the chronic stress-induced behavioral, biochemical, and adrenal structural changes mostly through its antioxidant and anti-inflammatory effects.